Analysis of Willingness to Pay Premium Apple Product Users in Indonesia - Indra Ayu Fatmala; Hendra Setiawan (Jurnal REKOMEN (Riset Ekonomi Manajemen), 2022)
The development of infuatry 4.0 and the covid-19 epidemic  is a major phenomenons that occurs in Indonesia. The existence of this phenomenon makes people are required to keep up with the developments of today's digitalized era. Along with this phenomenon, the development of gadgets is growing rapidly, various electronic companies are releasing their best products, including Apple Inc. Rapid development of the Apple brand makes the company's market share increase every year. Indonesia is also one of the countries that have many consumers who use the Apple brand. This becomes a question when a consumer is willing to pay higher for a gadget that Apple sells. The purpose of this study is to know how Willingness to Pay Premium appears on consumers who are influenced by Brand Love, Brand Commitment, and Brand Trust. All respondents are users of Apple products in Indonesia. Data analysis was performed using PLS (partial least square) 6.0. And the validity and reliability tests were carried out using factor analysis in SPSS 16, all indicators were valid and reliable. The results show that all hypotheses in this study can be accepted and have a positive effect.